The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3065087
|View full text |Cite
|
Sign up to set email alerts
|

High temperature phases in the 0.98PbZrO3–0.02Pb(Ni1/3Nb2/3)O3 ceramic

Abstract: The phase evolution with temperature in the 0.98PbZrO3-0.02Pb(Ni1/3Nb2/3)O3ceramic was investigated with dielectricpermittivity and polarization measurements, hot stage transmission electron microscopy, and high temperature x-ray diffraction. Below 190 °C, the ceramic is in the antiferroelectric phase with characteristic 14{110}csuperlatticediffractions. In this stage, typical antiferroelectric 180° domains were observed. Between 190 and 220 °C, an intermediate phase, which is characterized by 12{110}c-type su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
(52 reference statements)
3
12
0
Order By: Relevance
“…4(b), close examination of the hysteresis loop at 155 • C reveals that slight distortions, which are marked by two circles, occurred at ∼10 kV/cm. Similar distortions were found on the hysteresis loop in 0.98PbZrO 3 -0.02Pb(Ni 1/3 Nb 2/3 )O 3 and Pb 0.99 Nb 0.02 [Zr 0.57 Sn 0.43 ] 1−x Ti x ] 0.98 O 3 ceramics, and these have been attributed to the onset of electric field-induced AFE to FE transition [28,29]. Therefore, the 0.94PZ-0.06PMW ceramic is still in the AFE phase at this temperature and it should be noted that the distortions marked at 155 • C in Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…4(b), close examination of the hysteresis loop at 155 • C reveals that slight distortions, which are marked by two circles, occurred at ∼10 kV/cm. Similar distortions were found on the hysteresis loop in 0.98PbZrO 3 -0.02Pb(Ni 1/3 Nb 2/3 )O 3 and Pb 0.99 Nb 0.02 [Zr 0.57 Sn 0.43 ] 1−x Ti x ] 0.98 O 3 ceramics, and these have been attributed to the onset of electric field-induced AFE to FE transition [28,29]. Therefore, the 0.94PZ-0.06PMW ceramic is still in the AFE phase at this temperature and it should be noted that the distortions marked at 155 • C in Fig.…”
Section: Resultssupporting
confidence: 63%
“…It is apparent that replacement of the Zr 4+ ion by Mg 2+ /W 6+ ions decreases the driving force for the antiparallel shift of Pb 2+ ions, because they interrupt the translational symmetry. This interruption causes the appearance of an intermediate ferroelectric phase and similar behavior has been found in PZ-PNN ceramics [28].The DSC technique was used as the third tool to confirm the phase transition of PZ-PMW ceramics. Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Superlattice reflection peaks and a splitting (200) peak were observed at roughly 43° in the compositions, 0.02 ≤ x ≤ 0.04, ¼ ( hkl ). These results indicated that the crystal structure of ceramics is orthorhombic at the compositions, 0.02 ≤ x ≤ 0.04 . The XRD pattern for the composition, x = 0.06, showed a single (200) and split (111) reflection, indicating that the crystal structure was a rhombohedral perovskite.…”
Section: Resultsmentioning
confidence: 85%
“…The compositions 0.02 ≤ x ≤ 0.06 have the same crystal structure with pure PZ ( x = 0.00), i.e., an orthorhombic unit cell at room temperature. Furthermore, the ¼ ( hkl ) superlattice reflection peaks, representing the antiparallel shifts of Pb 2+ ions in the perovskite structure, were obtained for the compositions, 0.02 ≤ x ≤ 0.06 . However, their intensity became weaker with increasing BAN content.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation